Ongoing therapeutic trials and outcome measures for Duchenne muscular dystrophy - Govoni, Alessandra; Magri, Francesca; Brajkovic, Simona; Zanetta, Chiara; Faravelli, Irene; Corti, Stefania; Bresolin, Nereo; Comi, Giacomo P (Cellular and molecular life sciences : CMLS, 2013)
Muscular dystrophy is a heterogeneous group of genetic disorders characterised by progressive muscle tissue degeneration. No effective treatment has been discovered for these diseases. Preclinical and clinical studies aimed at the development of new therapeutic approaches have been carried out, primarily in subjects affected with dystrophinopathies (Duchenne and Becker muscular dystrophy). In this review, we outline the current therapeutic approaches and past and ongoing clinical trials, highlighting both the advantages and limits of each one. The experimental designs of these trials were based on different rationales, including immunomodulation, readthrough strategies, exon skipping, gene therapy, and cell therapy. We also provide an overview of available outcome measures, focusing on their reliability in estimating meaningful clinical improvement in order to aid in the design of future trials. This perspective is extremely relevant to the field considering the recent development of novel therapeutic approaches that will result in an increasing number of clinical studies over the next few years.